2000
DOI: 10.1093/jac/46.6.1033
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of antibiotic prescriptions from general dental practitioners in England

Abstract: The aim of this study was to determine the antibiotics prescribed by general dental practitioners (GDPs). Adult antibiotic prescriptions issued by GDPs from 10 Health Authorities (HAs) in England were analysed. The type of antibiotic prescribed, dose, frequency and duration were investigated. Most of the 17007 prescriptions were for generic antibiotics; nine different antibiotics were prescribed. Many practitioners prescribed antibiotics inappropriately with inconsistent frequency and dose, and for prolonged p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 5 publications
7
83
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11] The defi nitive treatment of a dentoalveolar abscess is drainage and removal of the cause of the infection. 14,17,18,[29][30][31][32][33][34][35][36][37][38][39] In the majority of cases this is the only treatment required.…”
Section: Current Prescribing Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11] The defi nitive treatment of a dentoalveolar abscess is drainage and removal of the cause of the infection. 14,17,18,[29][30][31][32][33][34][35][36][37][38][39] In the majority of cases this is the only treatment required.…”
Section: Current Prescribing Practicesmentioning
confidence: 99%
“…2,3 In 1997 GDPs issued over 3.5 million antibiotic prescriptions. 4 Studies in the United Kingdom have consistently shown that there is widespread variation in the prescribing habits of GDPs, with many prescribing inappropriately, with inconsistent dose and frequency and often for prolonged periods. [4][5][6][7][8][9][10] This was also shown to be the case when patients sought advice and treatment from their general medical practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published literature in this context related to either use of AMAs by dental practitioners in routine clinical practice or the success and failure of oral implants with or without AMAs [23][24][25][26][27][28][29][30]. Only one study from Jordan had specifically reported the use of AMAs by dentists performing oral implant surgery [31].…”
Section: Introductionmentioning
confidence: 99%
“…2 More common dental infections present in the form of pulpitis and periapical periodontitis, which require only operative measures like fillings, root canal therapy, or extraction if the tooth is not restorable. 3 Clinical situations that require antibiotic therapy on empirical basis are limited, and they include oral infection accompanied by elevated body temperature and evidence of systemic spread like lymphadenopathy and trismus. 4 There are also a limited number of localized oral lesions that are indicated for antibiotic use and these include periodontal abscess, acute necrotizing ulcerative gingivitis, and pericoronitis.…”
Section: Introductionmentioning
confidence: 99%